Exploring the Integrating Technology in ELT Curriculum - Wahidha, Rahma; Kardena, Absharini (Lembaga Yasin AlSys, 2024)
The curriculum must be purposefully arranged and divided into distinct programs in order to fulfill the nation's educational goals, which have been set by the Indonesian government. A major factor in determining what should be included in an educational curriculum is technology integration inside the curriculum. It is necessary to conduct research studies that examine the extent and effectiveness of technology integration in Indonesia's English curriculum. Because of this, it's imperative that instructors look into effective ways to incorporate technology into English curricula and stay up to date on the latest technological developments that can improve language acquisition. This work's primary research methodology is research library, which comprises a careful review of relevant books, articles, and research papers. The purpose of the English curriculum and how it may be applied to improve language instruction in indonesia